2002
DOI: 10.1096/fj.01-0848com
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal collagen fibrils in tendons of biglycan/fibromodulin‐deficient mice lead to gait impairment, ectopic ossification, and osteoarthritis

Abstract: Small leucine-rich proteoglycans (SLRPs) regulate extracellular matrix organization, a process essential in development, tissue repair, and metastasis. In vivo interactions of biglycan and fibromodulin, two SLRPs highly expressed in tendons and bones, were investigated by generating biglycan/fibromodulin double-deficient mice. Here we show that collagen fibrils in tendons from mice deficient in biglycan and/or fibromodulin are structurally and mechanically altered resulting in unstable joints. As a result, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
268
1
4

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 317 publications
(289 citation statements)
references
References 29 publications
16
268
1
4
Order By: Relevance
“…Even though decorin and biglycan are often found in different regions of the extracellular matrix and respond differently to growth factors [4], biglycan competes with decorin for the same binding site on type I collagen fibrils [4]. Thus, compensatory behavior of biglycan has been reported in Dcn −/− cell-seeded collagen gels and native tissues [16,34,35].…”
Section: Discussionmentioning
confidence: 99%
“…Even though decorin and biglycan are often found in different regions of the extracellular matrix and respond differently to growth factors [4], biglycan competes with decorin for the same binding site on type I collagen fibrils [4]. Thus, compensatory behavior of biglycan has been reported in Dcn −/− cell-seeded collagen gels and native tissues [16,34,35].…”
Section: Discussionmentioning
confidence: 99%
“…Mice were genotyped as described in ref. 26. KAT-4 anaplastic thyroid carcinoma cells (5 ϫ 10 6 ) or rat PROb (5 ϫ 10 6 ) colorectal cells were injected s.c. in the left flank of the mice and treated with Fc:T␤RII (10 mg/kg) as described in refs.…”
Section: Methodsmentioning
confidence: 99%
“…Fibromodulin controls collagen matrix structure in tendons and ligaments, and deficient mice show altered tissue organization with fewer and structurally abnormal collagen fiber bundles. The collagen fibrils are thinner (23), tendons and ligaments have reduced tensile strength, and the animals develop knee-joint instability and osteoarthritis (24)(25)(26). Fibromodulin mRNA has been detected in a variety of clinical malignancies, such as lung, breast, and prostate carcinomas (27)(28)(29).…”
mentioning
confidence: 99%
“…14 Additionally, modifications in ECM collagens, such as type VI and type X⌱ collagens, 15,16 and small ECM proteoglycans, such as asporin, biglycan, and fibromodulin, [17][18][19] can lead to the development of OA in the TMJ and in other joints. Furthermore, studies have reported that humans with genetic diseases involving defects in cartilage-related ECM genes, such as Marfan syndrome 20 and Ehlers-Danlos syndrome, 21 experience TMJ dysfunction.…”
Section: Fmodmentioning
confidence: 99%
“…18,19 Functionally, SLRPs can control ECM structure by interacting with the network of cartilage proteins and can mediate cell metabolism by binding to members of the transforming growth factor ␤ superfamily (TGF-␤). 17,23,24 Bgn and Fmod both bind to TGF-␤1, 23 a potent growth factor that regulates the formation and degradation of the ECM and maintains cartilage integrity in murine and human articular cartilage.…”
Section: Fmodmentioning
confidence: 99%